The impact of adhd on the performance of the profession of a professional soldier and other risk factors influencing the use of addictive substances in adolescence - Sedláčková, Simona; Hamplová, Lidmila; Pavlík, Vladimír (Vojenské zdravotnické listy, 2024)
Background: ADHD syndrome is still at the forefront of discussed diagnoses in children, and is a continuing phenomenon even into adulthood. At the same time, the development of substance and non-substance addictions at an early age is a constant problem. The phenomenon of behavioral disorders, hyperactivity, impulsivity, and inattention, resulting from the immature development of brain centers in children, often brings with it persecution from pedagogues and educators. For both children and adults, there is no suggested therapeutic procedure, except for medication, although it is possible to work with the given disorder with an appropriate bio-psycho-social approach. Subsequently, the developmental deficit persists into adulthood.Objective: The main objective of the work was to reduce the stigmatization of addicted persons and to point out all developmental factors leading to addictive behavior, one of which is ADHD and its manifestations. One of the other goals is to draw attention to the importance of therapy for people with ADHD and to reduce medication to a minimum, if this can be achieved, and at the same time to emphasize this developmental deficit in the recruitment of professional soldiers.Methods: It was a retrospective collection and analysis of anamnestic data from medical records, and further data was obtained through a questionnaire survey. The data was evaluated based on established scales. The method of surveying the analyzed data by the coefficient in the maximum value. The resulting values were obtained by summing the points within the individual risk factors.Results: The highest score in the evaluation of the answers, and therefore the highest influence on the later use of addictive substances, had a psychiatric illness in childhood (point evaluation 351), in second place with a number of 295 points was a serious illness in childhood as a significant risk factor, followed by learning disabilities (277 points) and a low level of sports skills.Conclusion: The information obtained should initiate an increase in attention in the framework of preventive examinations in children, to the expansion of screening in the framework of gross motor skills, movement skills, and the implementation of therapeutic methods through frequent training in connection with the development of brain centers. At the same time, attention should be focused on the treatment of children with ADHD by amphetamine-containing substances, which should have a decreasing tendency and expand efforts to implement therapeutic methods and knowledge of preventive medicine, such as sufficient exercise, healthy diet, and calm family background, which will lead to improved relationships in families to achieve a reduction in anxiety states in children.
Keywords: průzkumy a dotazníky; mužské pohlaví; ozbrojené síly; Military Personnel; Substance-Related Disorders; Mental Disorders; ženské pohlaví; poruchy spojené s užíváním psychoaktivních látek; návykové chování; Humans; Behavior, Addictive; Surveys and Questionnaires; hyperkinetická porucha; rizikové faktory; duševní poruchy; Attention Deficit Disorder with Hyperactivity; Female; Risk Factors; lidé; Male